Ministry Of Industry and Foreign Trade Decree No. 123 Of The Year 2013 On imposing An Export Duty On Certain Lead Articles = وزارة الصناعة والتجارة الخارجية قرار رقم 123 لسنة 2013 فى شأن فرض رسم صادر على بعض مصنوعات الرصاص - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.